Діяльність прокомуністичної УСДП на Західній Україні (1923–1924 рр.) - Райківський, Ігор Ярославович; Raikivskyi, Igor Y. (Східноєвропейський національний університет імені Лесі Українки, 2015)
У статті висвітлено діяльність УСДП після переходу в комуністичний табір на VI з’їзді 18 березня 1923 р. у Львові, до заборони партії польською владою в січні 1924 р. Звернуто увагу на причини й наслідки ліво-радикальної еволюції УСДП, основні напрями її прокомуністичної діяльності, створення клубу УСДП у сеймі. The article highlights pro-communist activity of the Ukrainian Social Democratic Party after its transition to the Radical Left Сamp at the VI. Party Congress of 18 March 1923 in Lviv. Among the reasons for the political evolution of the USDP was defeat of the Ukrainian revolution resulting in ideological disorganization among the social democrats, which was successfully used by the communists. After the Congress, the USDP became a legal extension of the Communist Party in Western Ukraine. In times of a deep ideological crisis in the national statehood camp (after the recognition of the Polish occupation of Eastern Galicia at the Conference of Ambassadors of the Entente, March 1923), the USDP became dominant in society, its influence expanding to Volhynia (Volyn region), Kholmshchyna (Kholm region) and some other regions, which led to banning of the party by the Polish authorities in January 1924. Some of the Ukrainian deputies in the Polish Sejm set up a separate club of the USDP, and in November 1924 joined the Polish communist faction.
Activity of the Pro-communist USDP in Western Ukraine (1923–1924)
Keywords: УСДП; партія; з’їзд; Головна управа; комуніст; USDP; party; congress; General council; communists